Digital Morphometrics of Leaf Shape and its Application to Species Differentiation in some Species of Argyreia Lour. (Convolvulaceae) - Oza, Kavi K.; Saiyed, Kamartaha I.; Raole, Vinay M. (Indian Forester, 2025)
Genus Argyreia belongs to the family Convolvulaceae and comprises flowering plants commonly known as silvervine or elephant creeper. These plants are native to tropical and subtropical regions, including parts of Africa, Asia, and Australia. Argyreia species are known for their large, attractive flowers and are often cultivated for ornamental purposes. Argyreia plants typically have simple and alternate, large, broad leaves. The leaves can vary in shape, often being ovate or cordate, and have prominent veins. Morphometric analysis of the leaves of eight (8) species of the genus Argyreia was carried out using Elliptic Fourier Analysis (EFA). Principal component analysis (PCA) was performed based on variance-covariance matrix. Resulting PCs are utilized to create a dendrogram via neighbour joining method using Euclidean distance. The dendrogram revealed three major groups among the presently analysed species of Argyreia. Group-I was comprised of four species i.e., A. pilosa, A. nervosa, A. boseana and A. sharadchandrajii. A. setosa, A. sericea and A. elliptica formed the second group. Due to different leaf shape A. cuneata has been placed in last group. Present study reveals the importance of morphometric analysis in species differentiation based on leaf shape and structure and can be used as additional identification tool when combined with other methods.